Performance analysis of Banyuwangi Regency judo athletes at the 8th East Java Provincial Sports Week 2023 - Sabatian, G. M. Dwiko Jaya; Khuddus, Lutfhi Abdil; Kafrawi, Fatkur Rohman; Supriyanto, Catur (Sriwijaya Journal of Sport, 2026)
Research Problems: Sport achievement requires systematic coaching supported by continuous evaluation to improve athletes’ technical and tactical performance. In combat sports such as judo, match performance is highly determined by the dominance of specific techniques applied effectively during competition. However, empirical data regarding technical dominance in regional-level competitions are still limited, particularly in the fighter category. Research Objectives: Therefore, this study aimed to analyze the dominance and distribution of techniques used by male judo athletes in the fighter category (-50 kg to +100 kg) at the 8th East Java Provincial Sports Week held in Mojokerto. Methods: This research employed a quantitative descriptive design using video-based match analysis. All recorded matches in the specified weight classes were systematically observed, and each successful technique was identified, classified, and tabulated to determine overall team technical trends. Results: The results revealed that throwing techniques (nage-waza) were more dominantly used compared to groundwork techniques (ne-waza), with several techniques such as seoi-nage and uchi-mata showing a higher frequency of successful execution. Conclusion: The findings indicate a technical preference pattern among athletes and highlight areas requiring improvement, particularly in variation and effectiveness of attack strategies. In conclusion, video-based match evaluation provides objective performance data that can be utilized by coaches to design evidence-based training programs and improve medal achievement in future competitions.